Visceral adiposity index is associated with premature ejaculation inversely: a cross-sectional study. (3rd July 2018) - Cakir, Suleyman Sami; Ozcan, Levent; Besiroglu, Huseyin; Dursun, Murat; Polat, Emre Can; Otunctemur, Alper; Ozbek, Emin
Abstract: Objective: Visceral adiposity index (VAI) is a novel indicator for the assessment of visceral obesity. In this study, we aimed to evaluate the relationship between VAI and premature ejaculation (PE). Materials and method: A total of 300 men were included in the study. Hundred and fifty men with PE and 150 men without PE (control). All men were evaluated for PE by premature ejaculation diagnostic tool (PEDT). VAI levels were calculated using body mass index (BMI), high density lipoprotein and triglyceride (TG) levels. Results: Mean age of the study groups was 34.3 ± 5.2 (30–60) years and the mean age of the controls were 35.9 ± 5.3 (30–60) years. The men with PE had lower BMI, TG levels, waist circumference (WC) and higher high-density lipoprotein-cholesterol (HDL-C) levels. Mean VAI level was 4.13 ± 0.7 in study group and 5.72 ± 1.6 in control group, respectively. VAI levels were statistically higher in men without PE ( p  < .001). Discussion: Our cross-sectional study demonstrated a negative correlation between VAI and PE. VAI is superior index for the evaluation and calculation the relationship between obesity and PE.